Advancing sustainable practices: Transient plane source methodology for analyzing thermophysical properties and enhancement wood as a thermal insulator - Rupali Tiwari; Vlastimil Boháč; Richard Hrčka; Anton Yi Ma; Mattias K. Gustavsson; Luigi Todaro; Petar Antov; Lubos Kristak (Developments in the Built Environment)
The research aims on thermophysical properties of an ancient silver fir wood using transient plane heat source method in three directions of wood defined under isotropic environment. Crucial parameters studied at room temperature include thermal conductivity, thermal diffusivity, thermal effusivity. Analysis of measured thermal responses were done with respect to the full range of time window interval and shortened interval chosen for fitting by model. The depth of heat penetration was investigated with an emphasis on the criteria for evaluating the thermal response published literature (Boháč et al., 2000). The findings support the challenges and understanding of the interaction of wood's orthogonality loaded when interacting with different heating powers (25, 40, 50, 70) (m W) with time (s). The inhomogeneous structure for different levels of thermal energy provided valuable insights into the complex nature of wood and essential for applications requiring heat management such as preservation, construction, material engineering, in specific direction of wood structure.